Effectiveness of a Dental Health Counseling for Parents in Preventing Caries among School-Going Children - Sarah Shami, Sadia Asif, Shajee Naveed, Huma Zahir, Shaista Zafar, Sabeen Fazal, Muhammad Naveed Uz Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the effectiveness of dental counseling for parents of young school-going children in increasing use of fluoride toothpaste and tablets thus, preventing dental caries. Methodology: An intervention study was conducted at the Department of Operative Dentistry, HBS Dental Hospital, Islamabad between December 2018 and June 2020. A total of 1605 school-going children aged 3 to 18 years were included in the study. During the study, 667 could not be reached after six months of study. For further comparison, a control group of 315 participants were also included. The control group included children between the age of 3-17 years with similar demographics as the intervention group. The intervention group was counseled about the use of fluoride toothbrushing and tablets.Brushing instructions and training were reinforced at each visit. Parents were further dismayed from providing their child with sugary beverages and snacks. Results: The study revealed that the frequency of consuming carbonated drinks (p=0.0005) and the rate of unsupervised toothbrushing (p=0.017) were statistically different. Consumption of carbonated drinks was significantly higher in the control group (p=0.0002). The proportions of unsupervised toothbrushing in the intervention group was significantly lower than the control (p<0.0001). The lack of fluoride toothpaste was significantly lower in the intervention group as compared to the control group (p<0.0001). Conclusion: The study found that dental health counseling was significantly associated with decreased dental caries and improved dental practices among school-going children. Proper counseling for use of fluoride toothpaste is effective in improving the dental health status among the pediatric population. Dental health practitioners should encourage parents to provide healthy diets to children and reinforce the habit of toothbrushing to the adequate prevention of dental decay. Keywords: caries, dental health, DMFT, fluoride, toothbrushing